2007
DOI: 10.1016/j.jcrs.2006.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the risk for endophthalmitis after cataract surgery: Population-based nested case-control study

Abstract: Nonoperative as well as operative factors are important in the prevention of endophthalmitis. Subconjunctival injection of antibiotics appears to be beneficial for endophthalmitis prophylaxis. The model showed that active risk management strategies designed to optimize hospitalization and chemoprophylaxis may reduce the incidence of endophthalmitis by up to 81%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 34 publications
0
48
1
1
Order By: Relevance
“…111,112 Although there are no prospective randomized studies to support the use of subconjunctival antibiotic prophylaxis, some clinical evidence suggests a protective benefit. Retrospective studies from Canada, 113 the U.K., 114 and Western Australia 115 found statistically lower rates of endophthalmitis when subconjunctival antibiotics were given. The largest of these studies (Western Australia) was a population-based case-control study covering 1980 to 2000.…”
Section: Subconjunctival Injectionmentioning
confidence: 96%
See 1 more Smart Citation
“…111,112 Although there are no prospective randomized studies to support the use of subconjunctival antibiotic prophylaxis, some clinical evidence suggests a protective benefit. Retrospective studies from Canada, 113 the U.K., 114 and Western Australia 115 found statistically lower rates of endophthalmitis when subconjunctival antibiotics were given. The largest of these studies (Western Australia) was a population-based case-control study covering 1980 to 2000.…”
Section: Subconjunctival Injectionmentioning
confidence: 96%
“…The largest of these studies (Western Australia) was a population-based case-control study covering 1980 to 2000. 115 However, because most of the surgeons used topical antibiotics and did not use intracameral antibiotics, there was insufficient statistical power to assess the relative benefits of these methods of antibiotic prophylaxis. One study directly compared intracameral and subconjunctival cefuroxime in a retrospective study of nearly 37 000 cases at a single eye hospital and found the intracameral route to be statistically superior.…”
Section: Subconjunctival Injectionmentioning
confidence: 99%
“…Other factors that are more controversial include increased patient age, corneal incision site and wound configuration. 42,43 The rates of endophthalmitis vary in retrospective audits. In the most useful study, the European Society of Cataract and Refractive Surgery performed a prospective randomised controlled trial of antibiotics in endophthalmitis, with the incidence in the placebo group being 0.34 per cent.…”
Section: Endophthalmitismentioning
confidence: 99%
“…[8][9][10] It would take thousands of operations with defined techniques and protocols to separate the important confounding variables. In this context, it is revealing that some studies suggest an increased incidence of endophthalmitis in the United States in a time frame that included conversion to sutureless small corneal incisions, introduction of the touted fourth-generation fluoroquinolones, and the discontinuance of subconjunctival antibiotics.…”
Section: J Cataract Refract Surg 2008; 34:505-509 Q 2008 Ascrs and Escrsmentioning
confidence: 99%
“…1 Ophthalmologists in Australia, New Zealand, and Pakistan are less likely to use topical antibiotics preoperatively and rarely use intracameral antibiotics, but they use subconjunctival antibiotics frequently and associate this with a reduced rate of endophthalmitis. 8,24,25 In United Kingdom studies, preoperative topical antibiotics were not commonly used but postoperative antibiotics (usually neomycin) were; antibiotic infusion during surgery was used by approximately 10% of doctors, intracameral antibiotics by 16%, and subconjunctival antibiotics by 68%. [26][27][28] Approximately 27% of European ophthalmologists use antibiotics in the irrigating solution, and 31% use intracamerally injected antibiotics.…”
Section: Absence Of Uniform Worldwide Approach To Prophylaxismentioning
confidence: 99%